Comparison of Heavy Metal Concentrations in Liver, Thigh, Breast and Gizzard Chicken Distributed in Shiraz, Iran: Risk Assessment - roghayeh nejati; Ameneh Nematollahi; mahsa hasanzadeh; Ali Khani Jeihooni; mehran sayadi (Fasa University of Medical Sciences, 2020)
Background & Objective: Today in the world, environmental pollution due to heavy metals, their accumulation in the food chain and their dietary exposure are considered as a serious danger. The purpose of this study was to measure the amount of nickel, arsenic, lead, zinc and cadmium in liver, thigh, breast and gizzard parts of chicken distributed in Shiraz. Materials & Methods: In this cross-sectional study, ten different brands of liver, thigh, breast and gizzard of chicken in Shiraz were collected from local markets and transferred to the laboratory with the cooling system. The concentration of heavy metals was measured by inductively coupled plasma atomic emission spectroscopy (ICP-OES). Results: The mean concentrations of arsenic, cadmium, nickel, lead and zinc in liver tissues were 0.017, 0.061, 0.031, 0.057 and 15.15 µg/kg, in thigh muscles 5, 6, 28, 46 and 3310 µg/kg, in the breast muscles were 6, 8, 180, 50 and 4510 µg/kg and in the gizzard were 7, 29, 9, 19 and 12810 µg/kg, respectively. Heavy metals concentration was higher in liver tissue than other tissues. Conclusion: The results indicated that the amount of heavy metals studied in chicken tissues are lower than world regulation standards. Also the results of risk assessment indicated that non-carcinogenic risk of these heavy metals due to chicken consumption is negligible while, the risk of carcinogenicity in the case of arsenic is higher compared to lead (relatively potential risk).